Strategi Pemasaran untuk Meningkatkan Penjualan Produk Program Prakerja di Universitas Muhammadiyah Bangka Belitung - Sumarno, Sumarno; Ridwan, Eka Muzalfitri; Sukma, Mega; Herliyanti, Verni; Wahyudi, Panca (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research aims to analyze the partial and simultaneous influence of product quality, pricing, and promotion on sales improvement at a Pre-Employment Training institution in Bangka Belitung. It also seeks to identify the most dominant factor affecting the sales increase of the Pre-Employment Program at Universitas Muhammadiyah Bangka Belitung. This quantitative research employed a sample of 50 participants who successfully enrolled in the program. Data collection methods included questionnaires, interviews, and documentation. The study utilized validity and reliability tests, multiple linear regression analysis, and hypothesis testing through t-tests, F-tests, and multiple determination coefficients (R²). The findings indicate that product quality, pricing, and promotion significantly influence sales improvement. The regression analysis revealed that 75% of sales variations are explained by the proposed model, demonstrating its effectiveness and relevance. Recommendations include focusing on strengthening promotion through social media and leveraging alumni testimonials to attract more participants.